The Effect of FDI on Clean Energy Consumption and CO2 Emissions: A Panel Data Analysis - Intan Karina Hapsari (Kementerian Luar Negeri Republik Indonesia, 2023)
The Indo-Pacific Economic Framework (IPEF) is pivotal in economic development of the Indo-Pacific region, providing a comprehensive blueprint for enhancing connectivity, trade, and investment. This research examines the third pillar of IPEF;